Severe Rhino-orbital Mucormycosis Infection of anIntensive Care Unit Patient: A Case Report - Tutak, Ayse Sahin; Findikli, Huseyin Avni; Aslan, Sefer; Turk, Bilge Aydin; Sirik, Mehmet; Bekfilavioglu, Garip (Archives of Clinical and Medical Case Reports, 2017)
Mucormycosis is an opportunistic fungal infection, which is occasionally seen in immunosuppressive patients, and has high morbidity and mortality rates despite treatment. The case is here reported of a patient admitted to our Intensive Care Unit (ICU) with diagnosis of diabetic ketoacidosis, acute kidney injury, acute cerebral infarct and rhino-orbital mucormycosis.This level of advanced rhino-orbital mucormycosis caused severe cutaneous and subcutaneous lesions has not been reported previously in literature and thus the case is evaluated in respect of the early diagnosis of mucormycosis and treatment.